Education Intervention "Caregivers Like Me" for Latino Family Caregivers Improved Attitudes Toward Professional Assistance at End-of-life Care. (July 2016) - Cruz-Oliver, Dulce M.; Malmstrom, Theodore K.; Fernández, Natalia; Parikh, Manas; García, Jessica; Sanchez-Reilly, Sandra
Objective: This study explores the ability of a culturally sensitive and case-based education intervention, Caregivers Like Me, to improve knowledge and attitudes regarding end-of-life (EOL) resources among Latino caregivers. Methods: A multicentered, cross-sectional study of Latino communities from different geographical regions and cultural backgrounds. An educational intervention was administered to family caregivers of Latino elders using a case-based video " telenovela " and pretest–posttest questionnaires. Results: Participants (N = 145) were mostly females (79%) with mean age of 56 ± 15 years. They reported active learning from intervention (91%) and high satisfaction (92%) with educational experience. Both caregiver stress self-awareness and willingness to accept professional help improved significantly from pretest to posttest. Conclusion: A culturally sensitive educational intervention increased Latino caregivers' self-awareness about caregiver stress and the need to consider professional assistance for EOL care.